Lenvatinib in multimodal therapy for unresectable radioactive iodine‐naïve differentiated thyroid cancer: A case report with literature review. Issue 10 (17th June 2022) - Kim, Hugh Andrew Jinwook; Nichols, Anthony Charles; Rachakonda, Ramanamurthy; Inculet, Richard; Sathya, Jinka; Rachinsky, Irina; Winquist, Eric
Abstract: Background: Patients with unresectable or metastatic differentiated thyroid carcinoma (DTC) are rare and require individualized therapy. This may require approaches not typically used in resectable disease. We report a patient treated with lenvatinib and external beam radiation therapy. Case: An 87‐year‐old woman presented with cT4N1aM1 papillary thyroid carcinoma with tracheal invasion. She was not a candidate for surgery, radioactive‐iodine, or radiation, so a trial of lenvatinib was offered. Her tumor showed clinical, biochemical, and radiological response after 5 months of lenvatinib, and she subsequently received external beam radiation. She enjoys good quality of life without evidence of cancer progression off therapy 21 months post‐initiation of treatment. Conclusion: Lenvatinib may be effective in RAI‐naïve advanced DTC patients as a component of individualized multimodal therapy when conventional options are not feasible.